Office 2010 Workflow Developing Collaborative Solutions - Collins, Mark; Enterprises, Creative (Apress : Imprint: Apress, 2010)
Workflow is the glue that binds information worker processes, users, and artifacts. Without workflow, information workers are just islands of data and potential. Office 2010 Workflow details how to implement workflow in SharePoint 2010 and the client Microsoft Office 2010 suite to help information workers share data, enforce processes and business rules, and work more efficiently together or solo. This book covers everything you need to know-from what workflow is all about to creating new activities; from the SharePoint Designer to Visual Studio 2010; from out-of-the-box workflows to state machine workflows. There's even a section on integrating external data with Business Data Services. Want solid knowledge of how to implement workflow in the new world of Office and SharePoint? Pick up Office 2010 Workflow today.